2020
DOI: 10.21203/rs.3.rs-19279/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graphene oxide nanofilm and the addition of L-glutamine can promote development of embryonic muscle cells

Abstract: Background: Formation of muscular pseudo-tissue depends on muscle precursor cells, the extracellular matrix (ECM)-mimicking structure and factors stimulating cell differentiation. These three things cooperate and can create a tissue-like structure, however, their interrelationships are relatively unknown. The objective was to study the interaction between surface properties, culture medium composition and heterogeneous cell culture. We would like to demonstrate that changing the surface properties by coating w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Low cytotoxicity and the interactive surface of graphene oxides create promising possibilities for use in drug delivery platforms. In some of the previous experiments, graphene oxide used as a scaffold stimulated the growth of some cells and inhibited other cells (cell cultures of different origin from chicken embryos) [ 50 , 51 ]. In other studies, it was demonstrated that graphene was up taken by cells [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low cytotoxicity and the interactive surface of graphene oxides create promising possibilities for use in drug delivery platforms. In some of the previous experiments, graphene oxide used as a scaffold stimulated the growth of some cells and inhibited other cells (cell cultures of different origin from chicken embryos) [ 50 , 51 ]. In other studies, it was demonstrated that graphene was up taken by cells [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%